2022
DOI: 10.7717/peerj.13713
|View full text |Cite
|
Sign up to set email alerts
|

Blood glucose, insulin and glycogen profiles in Sprague-Dawley rats co-infected with Plasmodium berghei ANKA and Trichinella zimbabwensis

Abstract: Background Plasmodium falciparum and tissue dwelling helminth parasites are endemic in sub-Saharan Africa (SSA). The geographical overlap in co-infection is a common phenomenon. However, there is continued paucity of information on how the co-infection influence the blood glucose and insulin profiles in the infected host. Animal models are ideal to elucidate effects of co-infection on disease outcomes and hence, blood glucose, insulin and glycogen profiles were assessed in Sprague-Dawley rats co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…The results revealed significant increases starting from the 7 th dpi and the highest value was measured on the 21 st dpi, then gradual decreases were detected starting from the 28 th dpi and the lowest significant value was detected on the 48 th dpi. This agreed with the reported of increase in insulin concentra-tion in T. zimbabwensis infected mice (Onkoba et al, 2016;Murambiwa et al, 2022). On the contrary, Wu et al (2009) observed hypoinsulinemia in T. spiralis-infected mice on the 8 th and the 18 th dpi when compared to uninfected mice then it returned to normal values.…”
Section: Discussionsupporting
confidence: 90%
“…The results revealed significant increases starting from the 7 th dpi and the highest value was measured on the 21 st dpi, then gradual decreases were detected starting from the 28 th dpi and the lowest significant value was detected on the 48 th dpi. This agreed with the reported of increase in insulin concentra-tion in T. zimbabwensis infected mice (Onkoba et al, 2016;Murambiwa et al, 2022). On the contrary, Wu et al (2009) observed hypoinsulinemia in T. spiralis-infected mice on the 8 th and the 18 th dpi when compared to uninfected mice then it returned to normal values.…”
Section: Discussionsupporting
confidence: 90%